Coordinated Modulation of Energy Metabolism and Inflammation by Branched-Chain Amino Acids and Fatty Acids - Ye, Zhenhong; Wang, Siyu; Zhang, Chunmei; Zhao, Yue (Frontiers in Endocrinology, 2020)
As important metabolic substrates, branched-chain amino acids (BCAAs) and fatty acids (FAs) participate in many significant physiological processes, such as mitochondrial biogenesis, energy metabolism, and inflammation, along with intermediate metabolites generated in their catabolism. The increased levels of BCAAs and fatty acids can lead to mitochondrial dysfunction by altering mitochondrial biogenesis and adenosine triphosphate (ATP) production and interfering with glycolysis, fatty acid oxidation, the tricarboxylic acid cycle (TCA) cycle, and oxidative phosphorylation. BCAAs can directly activate the mammalian target of rapamycin (mTOR) signaling pathway to induce insulin resistance, or function together with fatty acids. In addition, elevated levels of BCAAs and fatty acids can activate the canonical nuclear factor-κB (NF-κB) signaling pathway and inflammasome and regulate mitochondrial dysfunction and metabolic disorders through upregulated inflammatory signals. This review provides a comprehensive summary of the mechanisms through which BCAAs and fatty acids modulate energy metabolism, insulin sensitivity, and inflammation synergistically.